A continuous-wave and pulsed X-band electron spin resonance spectrometer operating in ultra-high vacuum for the study of low dimensional spin ensembles - Cho, F; Park, J; Oh, S; Yu, J; Jeong, Y; Colazzo, L; Spree, L; Hommel, C; Ardavan, A; Boero, G; Donati, F (AIP Publishing, 2024)
We report the development of a continuous-wave and pulsed X-band electron spin resonance (ESR) spectrometer for the study of spins on ordered surfaces down to cryogenic temperatures. The spectrometer operates in ultra-high vacuum and utilizes a half-wavelength microstrip line resonator realized using epitaxially grown copper films on single crystal Al2O3 substrates. The one-dimensional microstrip line resonator exhibits a quality factor of more than 200 at room temperature, close to the upper limit determined by radiation losses. The surface characterizations of the copper strip of the resonator by atomic force microscope, low-energy electron diffraction, and scanning tunneling microscope show that the surface is atomically clean, flat, and single crystalline. Measuring the ESR spectrum at 15 K from a few nm thick molecular film of YPc2, we find a continuous-wave ESR sensitivity of 2.6 · 1011 spins/G · Hz1/2 indicating that a signal-to-noise ratio of 3.9 G · Hz1/2 is expected from a monolayer of YPc2 molecules. Advanced pulsed ESR experimental capabilities including dynamical decoupling and electron-nuclear double resonance are demonstrated using free radicals diluted in a glassy matrix.